2003
DOI: 10.1002/maco.200390133
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and stainless steel in solutions of lithium nitrate in ammonia at moderate temperatures

Abstract: The lithium nitrate in ammonia solution has been proposed and demonstrated as a thermodynamically attractive working mixture for absorption heat pumps. A literature search failed to find corrosion studies of said solution. The corrosion of carbon and stainless steel in solutions of lithium nitrate in ammonia was studied for a series of concentrations and temperatures from 50 to 150 8C. The materials studied were found to be suitable for construction of absorption heat pump process equipment for this working mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Previous studies also report that an unspecified copper alloy is corroded in LNH while a stainless steel and a titanium alloy were not affected . For integration of LNH into a heat exchanger, it is of interest to examine interactions between this material and various metals and alloys which have some corrosion resistant properties . Furthermore, as various gaskets and o‐rings are potentially used in the construction of heat exchangers and could come into contact with the PCMs, it is also important to consider the compatibility of these materials with the salt hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also report that an unspecified copper alloy is corroded in LNH while a stainless steel and a titanium alloy were not affected . For integration of LNH into a heat exchanger, it is of interest to examine interactions between this material and various metals and alloys which have some corrosion resistant properties . Furthermore, as various gaskets and o‐rings are potentially used in the construction of heat exchangers and could come into contact with the PCMs, it is also important to consider the compatibility of these materials with the salt hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in water/lithium bromide absorption heat pump systems, corrosion can be a problem especially in the high‐temperature regions of the system and therefore, a careful choice of materials is needed . With common materials such as carbon and stainless steel, ammonia/lithium nitrate solutions have reasonably low corrosion rates at temperatures of up to 150°C …”
Section: Discussionmentioning
confidence: 99%
“…41 With common materials such as carbon and stainless steel, ammonia/lithium nitrate solutions have reasonably low corrosion rates at temperatures of up to 150°C. 42…”
Section: Corrosionmentioning
confidence: 99%
“…A study of the NH 3 /LiNO 3 mixture's corrosion on the carbon and stainless-steel materials was carried out by Heard and Ayala [53]. From the results, the authors verified that the three samples are suitable for the construction of an absorption heat pump, and an average corrosion rate of 0.05 mm per year was obtained.…”
Section: Nh 3 /(Lino 3 ) and Nh 3 /(Lino 3 + H 2 O) Solutionmentioning
confidence: 96%
“…C; X1 = 0.36) Gensch [49] P (X1 = 0.24-0.42) Blytas et al [50] P (X1 = 0.4-0.6) Infante-Ferreira [22] Correlations-Density, equilibrium vapor pressure, viscosity, and thermal conductivity. Uchibayashi et al [51] µ (T = −50.45-34.85 • C; X1 > 0.3); ρ (T = −50.45-19.85 • C) Aggarwal and Agarwal [52] P (T = −25.15-155.85 • C; X1 > 0.7) Heard and Ayala [53] Corrosion (49.85-149.85 • C) Libotean et al [19,20] P, µ, ρ, Cp (T = 20-80 • C; X1 = 0.35-0.65) Cuenca et al [21] k (T = 30- Even with this binary mixture, the absorption chiller presents a limitation of lithium nitrate's viscosity, leading to low heat and mass transfer. It was observed that the addition of water in the absorbent (LiNO 3 ) increases heat and mass transfer, besides increasing the affinity of the refrigerant (NH 3 ) with the absorbent, which produces a positive effect on the performance of the absorption chiller [18][19][20].…”
Section: Nh 3 /(Lino 3 ) and Nh 3 /(Lino 3 + H 2 O) Solutionmentioning
confidence: 99%